2006
DOI: 10.1158/1078-0432.ccr-06-0750
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Growth with Antiangiogenic Cancer Vaccine Using Epitope Peptides Derived from Human Vascular Endothelial Growth Factor Receptor 1

Abstract: Purpose: Antiangiogenic therapy is now considered to be one of promising approaches to treat various types of cancer. In this study, we examined the possibility of developing antiangiogenic cancer vaccine targeting vascular endothelial growth factor receptor 1 (VEGFR1) overexpressed on endothelial cells of newly formed vessels in the tumor. Experimental Design: Epitope-candidate peptides were predicted from the amino acid sequence of VEGFR1 based on their theoretical binding affinities to the corresponding HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…Generation of AG1-G1-Neo and AG1-G1-Flt1 Cell Lines-AG1-G1-Flt1 cells were established from a human angioma with the permission of the Ethics Committee for scientific research at the Institute of Medical Science, University of Tokyo (28). Briefly, an adult benign angioma was excised surgically, and the pEF1␣-SV40 large T antigen plasmid was introduced into the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Generation of AG1-G1-Neo and AG1-G1-Flt1 Cell Lines-AG1-G1-Flt1 cells were established from a human angioma with the permission of the Ethics Committee for scientific research at the Institute of Medical Science, University of Tokyo (28). Briefly, an adult benign angioma was excised surgically, and the pEF1␣-SV40 large T antigen plasmid was introduced into the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Recent technical advances have enabled the identification of various tumor-associated antigens (TAAs) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]; however, few of their epitopes are inducers of cytotoxic T lymphocyte (CTL) responses against tumors [22]. Several kinds of epitope have also been identified in patients with pancreatic adenocarcinoma [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Other endothelial membrane proteins involved in angiogenesis such as integrin b3, Tie-2, endoglin and fibroblast growth factor receptor-1 (FGFR-1) have been under preclinical studies and shown therapeutic potential in cancer treatment. 11 Dendritic cells pulsed with angiogenesis-associated antigens [12][13][14][15] and endothelial-dendritic cell hybrids 16 have also proved effective in angiogenesis inhibition. Because of the fact that angiogenic endothelial antigens remain largely unrevealed, fixed human umbilical vascular endothelial cells (HUVECs), 17 murine hepatic sinusoidal endothelial cells 18 or viable HUVECs 19 were used as vaccines to elicit autoimmunity that attacked tumor endothelium and hence inhibited tumor growth.…”
mentioning
confidence: 99%